2012
DOI: 10.1258/la.2012.011154
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of an early meaningful time point of bone parameter changes in application to an osteoporotic rat model with in vivo microcomputed tomography measurements

Abstract: The commonly used preclinical animal model of postmenopausal osteoporosis is the mature ovariectomized rat, whereby cessation of ovarian oestrogen production consequently results in bone volume reduction. The study aim was to precisely define the time course of structural changes resulting from ovariectomy and thereby reduce the time animals have to be treated to judge the effects of osteoporosis treatment. For this purpose, we assessed architectural changes by microcomputed tomography (mCT) during 10 weeks fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…This pattern is quite similar to that observed in OVX animals [14], as well as in postmenopausal osteoporotic women, in which a general increase in biochemical markers of This pattern is quite similar to that observed in OVX animals [14], as well as in postmenopausal osteoporotic women, in which a general increase in biochemical markers of…”
Section: Gomori's Trichrome Stainsupporting
confidence: 87%
See 1 more Smart Citation
“…This pattern is quite similar to that observed in OVX animals [14], as well as in postmenopausal osteoporotic women, in which a general increase in biochemical markers of This pattern is quite similar to that observed in OVX animals [14], as well as in postmenopausal osteoporotic women, in which a general increase in biochemical markers of…”
Section: Gomori's Trichrome Stainsupporting
confidence: 87%
“…The mature ovariectomized (OVX) rat is the most commonly used preclinical experimental model of postmenopausal osteoporosis, whereby cessation of ovarian estrogen production consequently results in bone volume reduction [14].…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that FBGCs grown for 4 days remain TRAP negative, but when the culture period was extended to 8 days, FBGCs became positive for TRAP staining. TRAP is an important marker of osteoclast activity [Keiler et al, 2012], and OCs from mice lacking TRAP staining were dysfunctional, resulting in an osteopetrotic phenotype [Hayman et al, 1996]. IL‐4, involved in the induction of FBGCs, suppresses RANKL‐mediated TRAP expression, but also increases TRAP expression in the absence of RANKL [Yu et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…16 Partial prevention of ovx-induced osteopenia by weight increase, although previously reported, 17 was not supported by several recent studies. 13,18 In addition, our data show irreversible changes within the bone microarchitecture (Figure 2, Supplementary Material 1).…”
Section: Evaluation Of the E2 Status And Influence Of E2 On Exercise mentioning
confidence: 57%